Evaluation of toxicity levels of micronutrient strengths on regeneration of grass pea under in vitro conditions. (7th May 2021) - Barpete, Surendra; Aasim, Muhammad; Khawar, Khalid Mahmood; Özcan, Sebahattin
Abstract: Grass pea is very sensitive to the deficiency or excessive amount of micronutrient elements like Fe, Zn, B, Mo that could disturb metabolic activities of the plants including inhibition in growth and their death. There is lack of information about the influence of these elements increased concentration in grass pea growth under in vitro conditions. Therefore, the present study aimed to investigate the availability and regeneration capacity of grass pea cv. Gurbuz using 1× (control), 2×, 3× 4× and 5× concentration of Fe, Zn, B and Mo in MS medium containing 1 mg/L thidiazuron and 0.25 mg/L naphthaleneacetic acid. The results demonstrated significant variations in regeneration capacity of the cultivar in respective treatments and showed inhibited response to enhanced concentration of Fe, Zn, B, and Mo supplies. All enhanced concentrations of Fe, Zn, B, and Mo treatments in MS medium resulted in poor shoot induction and reduced shoot counts per plants as compared to control. Each increase in concentration of Fe and B significantly increased shoot length, number of nodes/plants and internode lengths. Whereas, significant decrease in same traits were noted on MS medium containing enhanced concentrations of Zn and Mo. Root induction was completely inhibited using enhanced concentration of Fe and B. Whereas, root induction was promoted by Zn and Mo micronutrients in MS medium. The rooted shoots from Fe and Zn micronutrients content induced early flowering and maturity during hardening. The results showed that optimum micronutrient supply are key factors in successful regeneration of grass pea under culture conditions.